Electrocardiographic characteristics in the underweight and obese in accordance with the World Health Organization classification. (December 2015) - Kurisu, Satoshi; Ikenaga, Hiroki; Watanabe, Noriaki; Higaki, Tadanao; Shimonaga, Takashi; Ishibashi, Ken; Dohi, Yoshihiro; Fukuda, Yukihiro; Kihara, Yasuki
Abstract: Objective: It is clinically important to recognize how the underweight or obese affects electrocardiogram (ECG). We assessed the effects of body mass index (BMI) on QRS axis or R-wave heights. Methods: From daily outpatient electrocardiograms with sinus rhythm, 203 were selected. The patients were classified into four groups: underweight (< 18.5 kg/m 2 ), normal weight (18.5–24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ) and obese (≥ 30 kg/m 2 ). Results: With increasing BMI, QRS axis shifted rightward to leftward. There was a significant inverse correlation between BMI and QRS axis (r = − 0.60, p < 0.001). Multivariate linear regression analysis among age, female, BMI, hypertension, left ventricular internal dimension and left ventricular mass (LVM) revealed that BMI was an independent determinant of QRS axis (β = − 0.52, p < 0.0001). Although LVM increased with increasing BMI, R-wave heights in leads V4-5 were similar among the underweight, normal weight and overweight. R-wave heights in leads V4-5 were significantly lower paradoxically in the obese than other groups. With increasing BMI, Sokolow–Lyon index corrected by LVM decreased progressively. Conclusions: Our results suggest that the underweight or obese is strongly associated with QRS axis or R-wave heights.